Relationship between hearing, cognitive function, and quality of life in aging companion dogs. (6th August 2022) - Fefer, Gilad; Khan, Michael Z.; Panek, Wojciech K.; Case, Beth; Gruen, Margaret E.; Olby, Natasha J.
Abstract: Background: Elderly people with presbycusis are at higher risk for dementia and depression than the general population. There is no information regarding consequences of presbycusis in dogs. Objective: Evaluate the relationship between cognitive function, quality of life, and hearing loss in aging companion dogs. Animals: Thirty‐nine elderly companion dogs. Methods: Prospective study. Hearing was evaluated using brainstem auditory evoked response (BAER) testing. Dogs were grouped by hearing ability. Owners completed the canine dementia scale (CADES) and canine owner‐reported quality of life (CORQ) questionnaire. Cognitive testing was performed, and cognitive testing outcomes, CADES and CORQ scores and age were compared between hearing groups. Results: Nineteen dogs could hear at 50 dB, 12 at 70 dB, and 8 at 90 dB with mean ages (months) of 141 ± 14, 160 ± 16, and 172 ± 15 for each group respectively ( P = .0002). Vitality and companionship CORQ scores were significantly lower as hearing deteriorated (6.6‐5.4, 50‐90 dB group, P = .03 and 6.9‐6.2, 50‐90 dB group, P = .02, respectively). Cognitive classification by CADES was abnormal in all 90 dB group dogs and normal in 3/12 70 dB group and 11/19 50 dB group dogs ( P = .0004). Performance on inhibitory control, detour and sustained gaze tasks decreased significantly with hearing loss ( P = .001, P = .008, P = .002, respectively). In multivariate analysis, higher CADES score was associated with worse hearing ( P = .01). Conclusions and Clinical Importance: Presbycusis negatively alters owner‐pet interactions and is associated with poor executive performance and owner‐assessed dementia severity.